Antioxidant Activity, Phenolic Acid, and Flavonoid Composition of an Antiseptic Ointment Based on Aloe and Green Propolis and Its Potential for Preventing Mastitis in Dairy Cows - Sílvia Cristina de Aguiar; Solange Maria Cottica; Silvério Teixeira dos Santos; Juliana Maxiano da Fonseca; Luiza da Silva Leite; Mylena Leite da Silva (Veterinary Sciences)
Mastitis is a major challenge in dairy production, leading to decreased milk yield and quality due to increased somatic cell counts (SCCs). The overuse of antibiotics to treat this condition has raised concerns about antimicrobial resistance, prompting the search for alternative treatments. This study aimed to evaluate the antioxidant activity, phenolic acid, and flavonoid content of a natural antiseptic ointment based on green propolis and aloe vera. The phenolic and flavonoid composition was determined using ultra-high-performance liquid chromatography, revealing high concentrations of bioactive compounds, particularly in the green propolis extract. The antioxidant activity was assessed using the DPPH method, and the ointment was applied as a post-dipping treatment in dairy cows. Over a 56-day period, the SCC in cows treated with the ointment showed a significant reduction (p = 0.021) compared to the control group (1.94 and 2.21 log10 SCC/mL, respectively). These findings indicate that the combination of green propolis and aloe vera possesses promising antimicrobial and healing properties, making it an effective alternative for mastitis prevention in dairy cows.